New directions in Hispanic linguistics - Orozco, Rafael, 1959- (Cambridge Scholars Publishing, 2014)
This volume addresses some lacunae in Hispanic linguistic research by focusing on new scholarly directions, exploring understudied topics as well as speech communities, and presenting new takes on relevant linguistic and sociocultural issues. This publication answers questions which have emerged as a result of the rapid increase in Hispanic linguistic research since the latter part of the twentieth century or that have remained open in spite of it. With the rapid growth of Hispanic Linguistic ...